Imamship in Nigeria Police Formation’s Mosque: History, Appointment and Functions - Kolawole Odeniyi, Ismail; Kolawole Abdulsalam, Mikail (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract The position of imam in Islam is very essential because it is not only divine but also responsible for coordinating the Muslim ummah (community) in their spiritual and mundane affairs. Hence, the person to be appointed into this position must be known for religious veneration. Previous studies on Imamship in Nigeria have been limited to the community mosques with little attention to the mosques in Nigeria police. This is the vacuum identified by this current work. This work is therefore, designed to trace the history of Imamship in Nigeria police as well as the appointment and functions of Imam in the sector. Historical method was adopted while interpretive design was utilised. Primary and secondary sources were used. Primary sources included oral interviews conducted with 12 key informants. This comprises 4 (four) Imams, 4 (four) mosque functionaries and 4 (four) Ma‘mūm (the followers), aged between 30 and 60. Data were also collected through field visit observations. Secondary sources included books, journal articles, theses and internet materials. Findings revealed that the Nigeria police came into being in 1879 while Imamate section of the Sector was formed in April 1st 2006. Also, there are three types of Imams in the sector with observance of salāt as one of their major functions. Conclusively, literacy and certification in western and Islamic education are major criterions for the appointment of Imam into the sector. The paper recommended that Nigeria police authority should recruit more personnel into the Imamate section as there are shortages of personnel in the sector.